Matematické modely spolehlivosti v technické praxi - Schwarzenegger, Rafael (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Tato práce popisuje a aplikuje parametrické a neparametrické modely spolehlivosti na cenzorovaná data. Ukazuje implementaci spolehlivosti v metodologii Six Sigma. Metody jsou využity pro přežití/spolehlivost reálných technických dat.

This master’s thesis is describing and applying parametric and nonparametric reliability models for censored data. It shows the implementation of reliability in the Six Sigma methodology. The methods are used in survival/reliability of real technical data.
Mathematical Models of Reliability in Technical Applications
Keywords: Kaplan-Meier; Six Sigma; spolehlivost; přežití; Markov chain Monte Carlo; MCMC; Integrated Nested Laplace Approximation; INLA; Minitab; R; Kaplan-Meier; Six Sigma; Reliability; survival; Markov chain Monte Carlo; MCMC; Integrated Nested Laplace Approximation; INLA; Minitab; R